Experimental evidence on sharing rules and additionality in transfer payments - Esther Blanco; Natalie Struwe; James Walker (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
This study presents novel evidence showing that group payments distributed proportional to effort are as effective as payments targeted to individuals in increasing public good provision. The decision setting includes donors who make transfer payments to public good providers. The institutions under consideration are motivated primarily by payments for ecosystem services (PES), such as payments for climate protection. The decision settings, however, capture attributes of many forms of charitable giving where NGO type organizations support activities that provide public good externalities beyond those who directly benefit. Results are presented from two studies, varying the sharing rules for transfers among group members (equal share, proportional share, and individual targeting) and the presence of additionality, whereby transfers are received contingent on public good provision being at a level higher than in initial decision periods. The sharing rules studied result in significant differences in cooperation levels. Supported by higher transfer subsides, both the proportional share and targeted-transfers to individuals lead to greater public good provision relative to the equal share rule. Contrary to its alleged relevance in the literature, additionality does not lead to sustained increases in public good provision. Yet, additionality may improve the costeffectiveness of transfer programs by precluding transfer payments when the subsidies are not effective in increasing public good provision.
Keywords: D70; H41; C92; 330; Public good; Institution; Externality; Laboratory Experiment